Telomere interactions may condition the programming of antigen expression in Trypanosoma brucei. - Van der Werf, A (1990)
The AnTat 1.1 antigen type typically occurs late in a chronic infection by the EATRO 1125 stock of Trypanosoma brucei. The AnTat 1.1 gene, which is located 24 kb from a chromosome end, seems exclusively expressed by acting as a donor in gene conversion events targeted to the telomeric expression site. We report that this gene is sufficiently provided with the homology blocks required for recombination with the expression site, and is not interrupted by stop codons up to the 3' block of homology. A possible reason for its low probability of activation is an inverse orientation with respect to the proximal chromosome end, since, if correctly positioned, it is readily expressed at an early stage of infection, following gene conversion. This suggests that interactions between chromosome ends may precede and favour the rearrangements leading to antigenic variation.